Nilai Diagnostik Duke Treadmill Score untuk Mendeteksi Keparahan Lesi Koroner pada Pasien yang Terduga Penyakit Jantung Koroner Stabil - Ni Made Elva Mayasari; Irsad Andi Arso; Erika Maharani (Jurnal Kardiologi Indonesia, 2016)
Background: Duke Treadmill Score (DTS) is a well known score to stratify prognosis with good diagnostic value in predicting number of diseased coronary arteries in ischemic heart disease patient. DTS has also been shown to have a strong correlation with the severity of coronary lesion based on the Syntax score. However, the diagnostic value of DTS in predicting the coronary lesions severity based on Syntax score has not been well established.Methods: Cross-sectional study was performed in Dr. Sardjito General Hospital based on data from 1st January 2012. Patients with positive exercise test results and already had coronary angiography were included in the study. DTS was calculated based on the assessment of the exercise test result and Syntax score I was measured from the coronary angiography result.Results: There were 76 patients with average age of 56.64±7.41 year old consisting of 53 male subjects (70%) and 23 female subjects (30%). Hypertension was found to be the most common risk factors in 57 subjects (75%), dyslipidaemia in 33 subjects (43.3%), Diabetes Mellitus in 27 subjects (35.5%), smoking in 24 subjects (31.6%) and family history in 1 subject (1.3%). Subjects with high Syntax score and the low Syntax score were found in 30 subjects (39.5%) and 46 subjects (60.5%) respectively. In this study, the DTS diagnostic value in predicting high Syntax score was determined by the value of area under the curve based on the the Receiver Operating Characteristic (ROC) curve analysis was 92% (95% CI: 86%-97%, p<0.0001). Moreover, DTS with value -8.5had 83% sensitivity, 82% specificity, 75% positive predictive value, 88% negative predictive value, and 83% accuracy to predict high Syntax score.Conclusion: DTS has a good diagnostic value in predicting coronary lesions severity, particularly in patients with suspected stable coronary artery diseases. DTS value of -8.5 has shown to have the best cut point in this study.